Whither the Euro-Atlantic Space? Redefining Euro-Atlantic Security in a Post-Post-Cold War Era - Michael Hikari Cecire (e-cadernos ces)
The Ukraine conflict has exposed the fragility of both Ukrainian sovereignty and, more broadly, of the Euro-Atlantic security architecture as a whole. Western powers’ collective inability to effectively counter Russian aggression in Ukraine and along its periphery is a blow to the efficacy of the European post-Cold War era. Western retrenchment, meanwhile, only serves to effectively countenance Russian demands for spheres of influence and leaves Ukraine, as well as other periphery states such as Georgia and Moldova, isolated and vulnerable to Russian coercion. This strategy ultimately only undermines interstate norms and serves Russian neo-imperial designs. To restore the integrity of the Euro-Atlantic system, Western powers must play a more proactive role in defending periphery states’ sovereignty and revitalize predictable, realistic pathways for expansion into Euro-Atlantic structures.